Chronic Thromboembolic Pulmonary Hypertension – from Diagnosis to Intervention - Kazuhiko Nakayama; Noriaki Emoto (ACI (Acta Cardiologia Indonesiana), 2017)
Chronic Thromboembolic Pulmonary Hypertension – from Diagnosis to Intervention